2013
DOI: 10.1007/s00259-013-2617-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the myocardial activity acquired during exercise SPECT with a high-sensitivity cardiac CZT camera as compared with conventional Anger camera

Abstract: Myocardial activities acquired during exercise CZT SPECT are strongly influenced by body weight and tracer type, and are dramatically higher than those obtained using an Anger camera, allowing very low-dose protocols to be planned, especially for (99m)Tc-sestamibi and in non-obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…The tomographic count sensitivity is an additional critical parameter influencing both the acquisition time and the tracer's activity needing to be injected. This sensitivity is rather low on current SPECT-cameras, with only a fraction (10 −6 ) of the injected activities being detected within the myocardial area [6,14]. On Anger cameras, this fraction may be increased using a collimator with convergent geometry.…”
Section: Design Of the Czt Camerasmentioning
confidence: 99%
“…The tomographic count sensitivity is an additional critical parameter influencing both the acquisition time and the tracer's activity needing to be injected. This sensitivity is rather low on current SPECT-cameras, with only a fraction (10 −6 ) of the injected activities being detected within the myocardial area [6,14]. On Anger cameras, this fraction may be increased using a collimator with convergent geometry.…”
Section: Design Of the Czt Camerasmentioning
confidence: 99%
“…More importantly, the conventional cameras have very poor count sensitivity, which is further amplified by the poor extraction fraction of Tc99m. In a recent study by Verger et al, 19 it has been demonstrated that the conventional dual head scanner with high-sensitivity parallel hole collimators detects less than 1 ppm of the injected Tc-99m activity during the myocardial perfusion study. This is further exacerbated in the study by Klein et al by the use of stress-first low dose protocols (10 mCi stress dose).…”
Section: Is Conventional Mps Scanner Good Enough?mentioning
confidence: 99%
“…These improvements, in addition to allowing focused imaging of the heart and the use of new reconstruction algorithms, enable dynamic SPECT with kinetic analysis of 99m Tc-MIBI myocardial concentrations to be performed in animals and humans [17][18][19][20], providing incremental diagnostic information over perfusion data alone [17]. Further studies are needed to assess whether availability of transmission to correct for attenuation may enable better modelling of 99m Tc-labelled tracer kinetics.…”
mentioning
confidence: 99%